2017
DOI: 10.7860/jcdr/2017/26432.10423
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Parent to Child Transmission of HIV: Single Centre Experience of 14 years at Tertiary Care Hospital in Delhi, India

Abstract: The study highlights the practical aspects of policy implementation and operational issues involved in low resource country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
2
3
1
Order By: Relevance
“…The rate of parent to child transmission in our study was 2.56% with only 1 baby out of 39 tested positive at 6 weeks by DNA PCR. This was comparable to 3.3% observed by Dadhwal et al and 3.4% by Radhika et al 14,19 Only 1.92% babies were positive in study done by Gautam et al while as low as 0.7% were positive in study by Girma et al 15,20 Out of 39 infants in our study, no neonatal mortality was reported. Only 1 infant (2.5%) died at 4 months of age due to pneumonia; this was the only infant who tested positive at 6 weeks.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The rate of parent to child transmission in our study was 2.56% with only 1 baby out of 39 tested positive at 6 weeks by DNA PCR. This was comparable to 3.3% observed by Dadhwal et al and 3.4% by Radhika et al 14,19 Only 1.92% babies were positive in study done by Gautam et al while as low as 0.7% were positive in study by Girma et al 15,20 Out of 39 infants in our study, no neonatal mortality was reported. Only 1 infant (2.5%) died at 4 months of age due to pneumonia; this was the only infant who tested positive at 6 weeks.…”
Section: Discussionsupporting
confidence: 86%
“…16 On the contrary, Dadhwal et al and Radhika et al had 83.9% and 63.9% of their subjects chose top-feeding. 14,19 The decision of breastfeeding versus top-feeding differed depending upon study period because breastfeeding is now being promoted under WHO B+ regimen treatment for HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Most were in the 20-25 year age group, with 13.45% being under 20, thus it is imperative that knowledge about HIV and modes of spread be imparted from a younger age, along with sex education and safe sex practices, through mass media and awareness campaigns. [6][7][8] As seen in our study, Mohite et al, also reported an increase in the acceptance rate of pretest counseling and HIV testing, from 88.9% to 100% over 10 years. 9 The seroprevalence rate in our study was low compared to other studies, as shown in Table 4.…”
Section: Resultssupporting
confidence: 78%
“…In a study done by Shiradkar et al, 10.29% of seropositive women had an abortion and caesarean section rates declined from 50% to 31% from 2002 to 2011. 6 In a study done by Kwatra Stillbirth rate in our study was 3.23%, compared to 6.9% reported by Radhika et al, and 2% by Potty et al 8,16 There were 96.77% live births in our study as compared to 93.91% in the study done by Kwatra et al, and 93.12% reported by Shiradkar et al 6,7 We reported 100% ART coverage of antenatally registered HIV-positive pregnant women at our institute, 2013 onwards, which surpasses the target of >95% set by the WHO.…”
Section: Resultscontrasting
confidence: 45%
See 1 more Smart Citation